2016
DOI: 10.1155/2016/7843951
|View full text |Cite
|
Sign up to set email alerts
|

PEG-Immobilized Keratin for Protein Drug Sequestration and pH-Mediated Delivery

Abstract: Protein drugs like growth factors are promising therapeutics for damaged-tissue repair. Their local delivery often requires biomaterial carriers for achieving the therapeutic dose range while extending efficacy. In this study, polyethylene glycol (PEG) and keratin were crosslinked and used as sponge-like scaffolds (KTN-PEG) to absorb test proteins with different isoelectric points (pI): albumin (~5), hemoglobin (~7), and lysozyme (~11). The protein release kinetics was influenced by charge at physiological pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Different from the other proteins, it contains quite high cysteine content (5-10 mol%) that promotes its mechanical, chemical and thermal stability features due to the disulfide bonds present in their structures [19][20][21]. Like the other biopolymers from biological origins such as collagen, elastin and chitosan, keratin alone and mixed with other polymers have been also tested in various biomedical applications such as delivery of bioactive agents [22][23][24], wound healing [17,[25][26][27], and bone tissue engineering [28][29][30]. It has been almost genuinely proven that keratins are promising candidates as sustainable biomaterials due to their abundance, low cost and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Different from the other proteins, it contains quite high cysteine content (5-10 mol%) that promotes its mechanical, chemical and thermal stability features due to the disulfide bonds present in their structures [19][20][21]. Like the other biopolymers from biological origins such as collagen, elastin and chitosan, keratin alone and mixed with other polymers have been also tested in various biomedical applications such as delivery of bioactive agents [22][23][24], wound healing [17,[25][26][27], and bone tissue engineering [28][29][30]. It has been almost genuinely proven that keratins are promising candidates as sustainable biomaterials due to their abundance, low cost and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have observed that cell viability can be maintained when PEGDA or keratin biomaterials (e.g., a mixture of KAPs and KIFs) are used . Similar results were obtained in the present study, where a proliferation of cells was observed following a treatment with KAPs-PEGDA and KIFs-PEGDA gel extracts.…”
Section: Resultsmentioning
confidence: 73%
“…Reduced keratin proteins with free thiols can be gelled by reforming disulfide bonds. The photopolymerization of the thiolene reaction also links keratin with PEGDA . In this manner, the keratin and PEGDA networks are combined simultaneously to form the composite hydrogel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogel samples have been cut to small sizes (2cm x 2cm) and then placed in a dialysis bag and closed tightly by both sides using plastic clips then placed into a 50 ml tube and filled with 40 ml of PBS and pH 7.4 at 37°C. At regular time intervals (1, 2, 4, 6, 12, 24, 48, 72, and 96 h) was the measured quantity of released keratin from the hydrogels, 2 ml of the medium was withdrawn, replaced with the equivalent volume of fresh PBS and examined for the released keratin by the UV-VIS spectrophotometer (Shimadzu 1800, Japan) [24]. The keratin absorbance was read at λ 246 nm.…”
Section: 𝐸 = 𝜎 𝜀 (4)mentioning
confidence: 99%